A systematic review of lithium biology and pharmacology and toxicological evaluation of new organic lithium salts - I. Yu. Torshin; O. A. Gromova; V. V. Rastashansky; A. A. Garanin (Эпилепсия и пароксизмальные состояния, 2024)
Objective: to systematize scientific data on biomedical studies investigating trace element lithium over the past 70 years; evaluate toxic properties of lithium ascorbate (LiAsc) as an important promising candidate molecule.Material and methods. An analysis of 49,959 publications on lithium biomedical research retrieved from PubMed/MEDLINE database was carried out using modern data mining methods developed within the framework of topological approach to recognizing (Yu.I. Zhuravlev scientific school). Publications found by experts and not indexed in PubMed/MEDLINE were used in discussing the results of a systematic analysis of publications array retrieved from PubMed/MEDLINE. An experimental study of chronic 180 day-long LiAsc (at doses of 5, 50 and 150 mg/kg) toxicity was performed on 36 “Soviet chinchilla” rabbits by assessing local irritant action. Intoxication clinical picture, body weight dynamics, water and food intake as well as physiological, hematological and biochemical parameters were analyzed.Results. Classification and systematization of all currently available publications on lithium biology and medicine were performed. It was shown that pharmacological applications of lithium salts in mental disorders as well as lithium effects on simple sugars metabolism, lipid metabolism, blood pressure regulation, hematopoiesis, inflammation and tumor growth inhibition, neurotransmitter homeostasis, neurotrophic and neuroprotective molecular mechanisms as well as homeostasis of other electrolytes comprised promising fields of lithium drug research. The prospects for using organic lithium salts, particularly LiAsc, for various therapeutic goals were also discussed. 180-day-long oral administration of LiAsc at doses of 5, 50, 150 mg/kg resulted in no macroscopic signs of local inflammatory reaction while examining its local irritant effect.Conclusion. The lithium-ion effect on neurotransmitters promotes neuroprotection and reduces a risk of addiction. The antihypertensive, antiatherosclerotic, antidiabetic, antitumor and neurotrophic effects related to organic lithium salts may be beneficial in various therapeutic applications.